Who are ‘The Dead’ and When was the Gospel Preached to Them?: The Interpretation of 1 Pet 4.6 - Horrell, David G. 1963- (2003)
The interpretation of 1 Pet 4.6 which sees ‘the dead’ as Christians who heard the gospel during their lifetime but who have since died is becoming increasingly widely accepted, especially in recent commentaries in English. William Dalton's monograph Christ's Proclamation to the Spirits has been influential in promoting this view. However, despite its current popularity, there are serious problems with this interpretation, especially in its dependence on assuming a primitive eschatological context for 1 Peter. The view of the verse as referring to a proclamation made to people already dead, on the other hand, is more plausible than recent commentators suggest, and can be defended against their criticisms.